Coercive human rights : positive duties to mobilise the criminal law under the ECHR - Lavrysen, Laurens; Mavronicola, Natasa (London, England : Zed Books, 2020)
"Traditionally, human rights have protected those facing the sharp edge of the criminal justice system. But over time human rights law has become increasingly infused with duties to mobilise criminal law towards protection and redress for violation of rights. These developments give rise to a whole host of questions concerning the precise parameters of coercive human rights, the rationale(s) that underpin them, and their effects and implications for victims, perpetrators, domestic legal systems, and for the theory and practice of human rights and criminal justice. This collection addresses these questions with a focus on the rich jurisprudence of the European Court of Human Rights. The collection explores four interlocking themes surrounding the issue of coercive human rights: First, the key threads in the doctrine of the European Court of Human Rights on duties to mobilise the criminal law as a means of delivering human rights protection. Secondly, the factors that contribute to a readiness to demand coercive measures, including discrimination and vulnerability, and other key justificatory reasoning shaping the development of coercive human rights. Thirdly, the most pressing challenges for the ECtHR's coercive duties doctrine, including: - how it relates to theories and rationales of criminalisation and criminal punishment; - its implications for the fundamental tenets of human rights law itself; - its relationship to transitional justice objectives; and - how (far) it coheres with the imperative of effective protection for persons in precarious or vulnerable situations. Fourthly, the (prospective) evolution of the coercive human rights doctrine and its application within national jurisdictions."
Coercive human rights : introducing the sharp edge of the European Convention on Human Rights / Natasa Mavronicola and Laurens Lavrysen -- Positive obligations and the criminal law : a bird's-eye view on the case law of the European Court of Human Rights / Laurens Lavrysen -- Positive obligations and coercion : deterrence as a key factor in the European Court of Human Rights' case law / Paul Lemmens and Marie Courtoy -- Retribution through reparations? Evaluating the European Court of Human Rights' jurisprudence on gross human rights violations from a victim's perspective / Alina Balta -- Shaping coercive obligations through vulnerability : the example of the ECtHR / Corina Heri -- Criminal law responses to hate speech : towards a systematic approach in Strasbourg? / Stephanos Stavros -- Positive obligations in view of the principle of criminal law as a last resort / Nina Peršak -- Sowing a 'culture of conviction' : what shall domestic criminal justice systems reap from coercive human rights? / Mattia Pinto -- Coercive overreach, dilution and diversion : the potential dangers of aligning human rights protection with criminal law (enforcement) / Natasa Mavronicola -- Separating protection from the exigencies of the criminal law : achievements and challenges under Article 4 ECHR / Vladislava Stoyanova -- The limitations of a criminal law approach in a transitional justice context / Brice Dickson -- Preventive obligations, risk, and coercive overreach / Liora Lazarus -- Coercive human rights and unlawfully obtained evidence in domestic criminal proceedings / Kelly M Pitcher.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Online resource; title from digital title page (viewed on December 09, 2020).
Keywords: Convention for the Protection of Human Rights and Fundamental Freedoms -- (1950 November 5); Human rights; International law and human rights; International criminal law; Criminal law & procedure; Electronic books